Controlling corruption at the grassroots: lessons from a decentralised and participatory development administration - Mohanan, B. (1998)
The most important lesson that can be drawn form the Kerala experiment is that the minimisation of the role of the state as advocated by the World Bank is not the solution to cleanse the public life in Developing Countries and make it corruption free. The solution lies in effective state intervention as also in strengthening the civil society. Leaving everything to the market and entrusting the state with the role of a facilitator of market activities could only aggravate the situation further. In strengthening the civil society the lead role can be played by the new social movements such as ecological movements, Human rights organisations and movements that stand for the protection of the rights of women and children. The Non-Governmental organisation, whom the World Bank wants to promote, cannot work for controlling corruption due to the simple reason that majority of the NGO's are corrupt to the core. - Reproduced
Keywords: Decentralization - India; Corruption - India; Development administration - India; Corruption